Gallstones in New Zealand: composition, risk factors and ethnic differences. Issue 7 (17th September 2012) - Stringer, Mark D.; Fraser, Sara; Gordon, Keith C.; Sharples, Katrina; Windsor, John A.
Abstract Background Gallstone disease is a worldwide problem causing morbidity, mortality and a drain on health‐care resources. This prospective study aimed to investigate the spectrum of gallstone types in New Zealand and relate these to known risk factors. Methods Gallstone samples were collected from 107 patients undergoing surgery for gallstone disease at Auckland City Hospital between June 2009 and June 2010. Detailed chemical analyses were performed using Fourier Transform Raman spectroscopy. The relationship between gallstone type and age, gender, ethnicity, obesity and positive family history were analysed. Results Median age was 51 years (range 19–88), 75 (70%) were female, one third were obese (body mass index ≥ 30) and 41% had a positive family history. Major ethnic groups were European (51%), Asian (23%) and Māori/Pacific (18%). Gallstone types included pure or mixed cholesterol stones (74%), black pigment stones (20%) and brown pigment stones (5%). Asians had a higher proportion of black pigment stones and NZ Europeans had more cholesterol and mixed cholesterol stones (odds ratio 3.6 (95% CI 1.1 to 11.5)). The frequency of cholesterol/mixed cholesterol stones was not significantly different between NZ Europeans and Māori/Pacific groups (P = 0.7). Black pigment stones were more common in older patients (mean 68.0 years compared with 47.6 for cholesterol/mixed cholesterol stones) (P = 0.0001). There was no significant relationship between stone type and family history (P = 0.16) or gender (P = 0.17). Conclusion This novel prospective study highlights risk factors and ethnic differences in gallstone composition in New Zealand. These may be important when considering gallstone prevention strategies.